Chromosomal mapping of ribosomal clusters and telomeric sequences (TTAGG)n in nine species of lobsters (Crustacea, Decapoda) - S. SALVADORI; F. DEIDDA CANELLES; L. CARUGATI; R. MELIS; E. COSTA; M. SIBIRIU; E. COLUCCIA (The European Zoological Journal, 2023)
Lobsters are ubiquitous, economically important decapod crustaceans with apparently conflicting evolutionary relationships. Here, we describe the chromosomal location of the major (45S rDNA) and minor (5S rDNA) ribosomal gene families in four species of Astacidea and five of Achelata, using two-color FISH. The major ribosomal family is located in 4–16 sites per diploid chromosome set, with Nephrops norvegicus (Nephropidae) showing the highest number described so far in Decapoda. The 5S rDNA is located in two sites in eight species; only in the crayfish Procambarus clarkii the 5S FISH signals were detected in four sites together with additional weaker signals. Furthermore, in N. norvegicus the minor ribosomal genes are syntenic with one major ribosomal cluster. Moreover, we located by two-color FISH the pentanucleotide (TTAGG)n telomeric repeat in the Nephropidae studied, showing the occurrence of a colocalization with 45S ribosomal sequences in Homarus gammarus. The comparison of chromosomal locations of repetitive sequences in Mediterranean, Atlantic, and South African lobster species as well as in marine and freshwater ones provides information on chromosomal evolution and cytotaxonomy of Decapoda.